2000
DOI: 10.1007/s11881-000-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reading-spelling connection as locus of dyslexia in Chinese

Abstract: This paper advances the argument that in learning to read/spell Chinese characters and words, it is important for learners to understand the role of the component parts. These constituents consist of phonetic and semantic radicals, or bujians, made up of clusters of strokes in their proper sequence. Beginning readers/spellers need to be sensitive to the positional hierarchy and internal structure of these constituent parts. Those Chinese children diagnosed with developmental dyslexia tend to have more difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…The basic graphic unit in Chinese, the character, represents a syllable as well as a morpheme. Each character is made up of radicals (or bujians), which consist of different strokes arranged sequentially, and combined in different configurations in characters (Leong, Cheng, & Lam, 2000). There are eight basic types of strokes (Law, Ki, Chung, Ko, & Lam, 1998).…”
Section: Chinese Writing Systemmentioning
confidence: 99%
“…The basic graphic unit in Chinese, the character, represents a syllable as well as a morpheme. Each character is made up of radicals (or bujians), which consist of different strokes arranged sequentially, and combined in different configurations in characters (Leong, Cheng, & Lam, 2000). There are eight basic types of strokes (Law, Ki, Chung, Ko, & Lam, 1998).…”
Section: Chinese Writing Systemmentioning
confidence: 99%
“…This is different from the English writing system that requires writers to produce written words from the fixed set of 26 letters on the horizontal grid lines (Figure 1). Leong et al (2000) suggested that the complex orthographic rules in Chinese writing system is particularly challenging for Chinese children with dyslexia to acquire the basic writing skills.…”
Section: Nature Of Writing To Dictation and Handwriting In Chinese Lamentioning
confidence: 99%
“…Many school activities also expect children to develop effective handwriting skills to transcribe printed information on the texts so as to produce written answers on papers (Feder & Majnemer, 2007). In a Chinese school population, children with dyslexia are more commonly observed with persistent difficulties in acquiring basic writing skills than reading skills (Leong, Cheng, & Lam, 2000). This study aimed at identifying the factors that may possibly explain different levels of writing difficulties among Chinese children with dyslexia.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the child might need to call on a visual-spatial type of short-term memory system as well as a phonological working memory system (see Gathercole & Baddeley, 1993). Thus, for Chinese children with dyslexia, while there could be phonological deficits, there might also be other difficulties that are connected with the complexity of the Chinese characters and the different combinations that they form, suggesting that the listening-reading connection might assume less importance relative to other connections involving the four basic language skills (see also Leong, Cheng, & Lam, 2000).…”
mentioning
confidence: 99%